The Significance of Manual Wheelchairs: A Comparative Study on Male and Female Users - Lanutti, Jamille N.L. [UNESP]; Medola, Fausto O. [UNESP]; Gonçalves, Diego D. [UNESP]; da Silva, Luciana M.; Nicholl, Anthony R.J.; Paschoarelli, Luis C. [UNESP] (Elsevier, 2015)
As one of the most representative assistive technology devices, the wheelchair has many peculiar aspects in its daily usage. Therefore, the wheelchair cannot be thought of only as a mobility device, and ergonomic investigation should include also aesthetics and symbolic aspects. This study was aimed at investigating the influence of gender on the users’ perceptions about the significance of their own wheelchair. The sample comprised ten manual wheelchair users, being five men and five women. Subjects were asked to rate in a seven-point scale their perceptions about each pair of opposite adjectives, taking into account their experience with their own wheelchairs. The mean and standard deviation values were obtained for each pair of adjectives and then compared between the two groups of subjects by using parametric and non-parametric tests, according to the normality of the data. The results show that, in general, men's perceptions about their wheelchairs were more positive than women's in both practical and symbolic functions. Significant difference between gender was found with the pairs of adjectives including/excluding (p=0.003) and efficient/inefficient (p=0.038). Such differences may reveal underlying problems that female users experience in daily wheelchair usage and, ultimately, reflect the social consequences of this. Knowledge about the significance of assistive devices is important to provide a view not only on practical, but also aesthetic and symbolic aspects of the product, thus benefiting designers in developing products that best meet the users’ needs and expectations.
Keywords: Assistive technologies; Ergonomics; Semantics; User's perceptions; Wheelchairs